Pemberdayaan kepada Masyarakat di Bank Sampah Mulya Sejahtera melalui Pilah Sampah - Handajani, Mudjiastuti; Istianah, Istianah; Budiningrum, Diah Setyati; Purwanti, Hani; Syahrial, Erialdi Bin; Sofaniadi, Safrinal; Sabila, Arien Zahra Sal; Khoirul, Muhammad (Jurnal Pengabdian KOLABORATIF, 2026)
The main problem in Plalangan Village, Gunungpati Subdistrict, Semarang City, is the low awareness and practical skills of residents in sorting waste at the source and the suboptimal utilization of household composter facilities. This community service activity aims to increase residents’ awareness, knowledge, and practical skills in sorting waste and processing organic waste independently. The implementation method applied is participatory training combining interactive education, in the form of socialization regarding the 3R (Reduce, Reuse, Recycle) concept and the Clean Semarang Program, followed by demonstrations and practical simulations of waste sorting using pilot props. The evaluation results showed a highly positive impact, where the participants’ average level of cognitive understanding experienced a highly significant increase from 42% in the pre-test to 86% in the post-test. Furthermore, residents successfully mastered practical skills in upstream waste sorting, creating biopori infiltration holes, and operating simple composters. These skills are useful for converting organic waste into compost to support the greening of household yards while simultaneously improving the local community’s economic value through the Mulya Sejahtera Waste Bank. In conclusion, the training program in this village has proven effective in transforming community behavior toward sustainable and independent household-based waste management.